TEACHING AND ASSESSING SPEAKING (Ustozlar uchun, 2025)
This paper explores the principles, methods, and challenges involved in teaching and assessing speaking skills in second language classrooms. Speaking is a productive skill that requires linguistic, sociolinguistic, and strategic competence. The study highlights effective classroom techniques such as communicative activities, task-based learning, and interaction-based instruction. It also examines major speaking assessment types, including formative, summative, performance-based, and standardized tests. The paper emphasizes the importance of reliability, validity, fluency, accuracy, and communicative effectiveness in evaluating speaking proficiency. Overall, it provides teachers with theoretical insights and practical strategies for enhancing students’ oral communication skills.